Critical evaluation of a position sensorless control technique for the reluctance synchronous machine drive - Smuts, Johan L. (Johan Leodolf) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2001.